2017
DOI: 10.1155/2017/9314689
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Mesoscopic Parameters and Mechanical Properties of Granular Materials upon Loading

Abstract: Biaxial tests of granular materials under different lateral pressures were numerically simulated to study both the macromechanical behavior and evolution of mesoscopic parameters, including the coordination number, degree, clustering coefficient, and average shortest path length, which can provide information bridging mesoscale to macroscale of the mechanical properties of granular materials in a different and new way. The analysis results demonstrate that, with the increasing lateral pressure, there is a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The properties of the network can be researched through the complex network method. And many of the recent developments of this method have taken place in sociology, biology, and in the field of granular materials [28,[43][44][45][46]. Studies have found that the 3 loops dominate the topologic structure at the mesoscale and 3 loops in a network is associated with frustrated rotations of particles and as such to stability [47,48].…”
Section: Modified Clustering Coefficientmentioning
confidence: 99%
“…The properties of the network can be researched through the complex network method. And many of the recent developments of this method have taken place in sociology, biology, and in the field of granular materials [28,[43][44][45][46]. Studies have found that the 3 loops dominate the topologic structure at the mesoscale and 3 loops in a network is associated with frustrated rotations of particles and as such to stability [47,48].…”
Section: Modified Clustering Coefficientmentioning
confidence: 99%
“…Based on the concept of complex networks Tordesillas et al [20] analyzed the evolution of the contact networks. The contact network was particularly useful in describing particle interactions [21][22][23] which can quantify the changes in the internal structure of granular assemblies. Radjai et al [24,25] found that the contacts carrying above-and below-average normal forces have different effects on force transmission and work dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the study achievements of mesoscopic structure for cohesionless soil is quite rich, most of the research results only from a certain parameter of the mesoscopic structure (such as the fabric tensor [1], force chain [2]), with few studies on the evolution of contact networks in the process of loading. Recently, we have studied the evolution of mesostructure of soil samples from the perspective of complex network concepts [3,4,5], which can provide a new insight to investigate the physical mechanism of granular materials from meso to macro scale, and will be done here to explore the evolution of force chain and contact network of non-cohesive soil.…”
Section: Introductionmentioning
confidence: 99%